History of Civilization and Economical (Business) Third Period Shah Sayid Ridha - Arpiati (Budapest International Research and Critics University, 2022)
Sayyid Muhammad Rashid Rida, in his life, has to give discordant to others with three types of thinking, namely religious thought, educational thought, knowledge, and political thought. Temporary that in the field of economic reform is not explained so clearly, but in a study, this researcher uncovered that many of the works produced by Shah Ridha one of the works that have been printed up to more than 1000 are the al-Manar magazine which contains interpretations of the Koran that are easily understood by the general public. Rashid Ridha's other works are no less interesting than his previous works, even with several published works and succeeded in spreading among the public; that is how Rashid Rida broadcasts his religion through trading with the works he created with the teacher Muhammad Abduh.